The Dynamics of the Application of Stoning Criminal Law from an Islamic Perspective in Indonesia and other Muslim Countries - Setiawan, Rizal Ahmaludin; Rohmah, Siti Ngainnur; Al Munawar, Kholil; Almaarif, Azhar; Dewanti, Tri Mustika (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2025)
The stoning punishment, despite having a legal basis in Islam, sometimes sparks controversy as it clashes with modern values such as human rights and national constitutions. This study analyses the dynamics of implementing stoning as a criminal punishment from an Islamic perspective, particularly in Indonesia. It compares it with other Muslim-majority countries such as Saudi Arabia, Pakistan, and Malaysia. This research employs a qualitative method, examining literature in the form of scholarly articles, legal documents, and relevant books. The findings indicate that the enforcement of stoning as a criminal punishment, both in Indonesia and in other Muslim countries, has sparked significant debate and even international condemnation for allegedly violating human rights. At first glance, stoning may appear cruel, but behind this punishment lies a crucial lesson for society—it serves as a deterrent to prevent others from committing adultery. In different countries, the implementation of stoning laws varies depending on the legal system, social acceptance, and interpretations of Islamic law. In Indonesia, the stoning punishment is only enforced in the province of Aceh. The position of Islamic criminal law in Indonesia is influenced by the principle of Bhinneka Tunggal Ika (Unity in Diversity), which emphasises the nation's cultural and religious diversity. Consequently, the application of Islamic criminal law must align with the principles of democracy, human rights, justice, and national diversity.Keywords: Islamic Criminal Law; Stoning; Objectives of Sharia (Maqasid al-Syariah)